Peran Preservasi Kuratif dalam Menjamin Keselamatan dan Pelestarian Arsip Statis - Rapita, Rapita (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
This paper aims to determine the role of curative preservation in ensuring the safety and preservation of static archives. The method used in this research is descriptive qualitative with data collection techniques using library studies. The results of the study found that curative preservation plays a very important role in ensuring the safety and preservation of archives because the actions and instructions contained in it can repair and maintain archives that have started or have been damaged. So that these actions and instructions can be used as guidelines by any archival institution to repair and maintain the static archives they have.